The coral island - Ballantyne, R. M. (Bancroft books, 1977)
Three English boys, shipwrecked on a deserted island, create an idyllic society despite typhoons, wild hogs, and hostile visitors. Then evil pirates kidnap one of the youths whose adventures continue among the South Sea Islands.